INTEGRASI PENDIDIKAN KARAKTER DALAM PERKULIAHAN BAHASA INGGRIS: STUDI ANALISIS MATA KULIAH UMUM (MKU) UNIVERSITAS KUSUMA HUSADA SURAKARTA - Syukur, Bambang Abdul (FPIPSKR Universitas PGRI Semarang, 2023)
The article aimed to describe how character values were integrated into the teaching English process. Type of research adopted qualitative with descriptive methods. Data collection employed observation and literature study. Data analysis included data collection, data reduction, data presentation, and creating a conclusion. The results obtained (1)an overview of the implementation of character education at the higher education level through English lessons. and (2) integrated character values in learning English. The integration process was performed by incorporating character values, especially in the characteristics of patriotism, communication, avid reading, curiosity, democracy, and independence in the form of planning (syllabus and lesson plans), learning methods, teaching materials, learning media, classroom implementation, monitoring, and evaluation of overall activities.